ANALYSIS OF FIQH SIYASAH ON THE CONCEPT OF ISLAMIC GOVERNMENT ACCORDING TO HASAN AL-BANNA'S THINKING - Hanafie, Ahsandy Rizky Fadhlansyah; Halimang, St (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
Hasan Al-Banna as the founder of the Muslim Brotherhood put forward the concept of government to harmonize religion and state. The concept of government contained in Hasan al-Banna's theory imitates the form and nature of the leadership of the Prophet Muhammad. This study aims to determine the thought pattern of Hasan al-Banna in the concept of Islamic government and also to find out the relevance of Hasan al-Banna's government to the government in Indonesia. This research uses library research, and the nature of this research is descriptive-analysis. The data that has been collected is then analyzed using qualitative inductive analysis. The results of this study indicate that fiqh siyasah in this case responds to Hasan Al-Banna's concept of thinking about Islamic government in line with the principles of government according to Fiqh Siyasah because Islamic government is a government that is upright on Islamic law which is sourced from the Qur'an and Sunnah. Then the relevance of Hasan Al Banna's Islamic government to government in Indonesia is that the Islamic government system in Indonesia is increasingly finding its vitality because the construction of the government system that has been implemented so far seems to have failed to build a harmonious and humanist state order.